Engineered Fe3O4/MgO/activated carbon nanocomposites as bifunctional materials for environmental remediation - Zainullah, Muhammad; Setiana, Mina Devika; Rahmawati, Febriana; Rokhimah, Alfi Qoidatul; Zhafirah, Aura Gitta; Hidayat, Nurul; Amrillah, Tahta; Fen, Yap Wing; Taufiq, Ahmad (KeAi Publishing Communications, 2026)
In recent years, increased industrial activity, without adequate wastewater management, has significantly contributed to rising levels of bacterial and heavy metal contamination in environments. Therefore, effective solutions for environmental remediation are required, particularly using economical, effective, efficient, and environmentally friendly. To address this issue, this research developed magnetite/magnesium oxide/activated carbon (Fe3O4/MgO/AC, FOMAC) nanocomposites that integrate dual functionalities within a single system, offering a more efficient and practical alternative compared to conventional materials. Interestingly, the Fe3O4 and AC nanoparticles were derived from natural materials, iron sand and coconut shells, which are environmentally friendly materials that contribute to reducing toxic reagents, decreasing environmental footprints, and supporting sustainable pollution mitigation. The FOMAC nanocomposites were prepared via synergistic coprecipitation, chemical activation, and sonication methods. The prepared nanocomposites were characterized by XRD, FTIR, SEM-EDX, VSM, BET, AAS, and well diffusion. The data analysis showed that FOMAC possessed an inverse spinel cubic structure for Fe3O4 and a face-centered cubic structure for MgO with crystallite sizes of 12.85 nm and 36.06 nm, respectively. FOMAC was confirmed to have spherical and chunk morphology with nanometric average particle sizes. The functional groups of Fe-O (octahedral and tetrahedral sites), Mg-O, and C=C were identified at wavenumbers of 452, 682, 804, and 1399 cm–1, respectively. FOMAC had a high specific surface area of 30.6802 m2/g and exhibited superparamagnetic properties with a saturation magnetization of 10.006 emu/g. Interestingly, FOMAC exhibits excellent performance against E. coli and S. aureus bacteria, with inhibition zone diameters of 12.49 mm and 14.10 mm, respectively. Moreover, FOMAC has an adsorption efficiency of 63.40% for Pb(II) removal. Interestingly, FOMAC had an adsorption efficiency up to 98.83% for Cd(II) removal. Thus, these findings indicate that FOMAC provides a scalable and sustainable materials strategy for environmental remediation, thereby improving environmental quality and reducing health risks to society from microbial and heavy metal (Pb(II) and Cd(II)) contamination.